Cistercian Architectural Heritage as Cultural Landmarks - Martins, Ana Maria Tavares (2012)
This approach will be based on the Cistercian heritage in Portugal through a systematic analysis of the Cistercian existences, its appropriation and insertion in the territory. So that this contex-tualization to be possible, it’s necessary to proceed to the identification of the territorial key-words, which provided the existence of these architectures in Portugal, as well as its integration, its transformation and its permanence in the territory. The geographical, topographical and his-toric approaches will be providing a typology scheme for the chosen sites. The relationship be-tween Cistercian architecture and actuality is deeply linked to the subject of how to rehabilitate this heritage. Which are the actions and the strategies to be used? How the monastic heritage does interact with the contemporary urban or rural territory? How an ideal becomes an architec-tonic reality? How the Cistercian architectural heritage becomes a cultural landmark?